Faktor prediktor malnutrisi rumah sakit pada anak di RSUP Dr. Sardjito - Arsyad, Muhammad Tsani; Nurani, Neti; Indrawanti, Ratni (Jurnal Gizi Klinik Indonesia, 2023)
Predictors of pediatric hospital acquired malnutrition in a Sardjito HospitalBackground: In hospitalized children, nutrition is essential for the healing process as well as for reaching adequate growth. Hospital-acquired malnutrition (HAM) is declining in children’s body weight during hospitalization. The impact of undetected HAM including an increase in length of stay, increase in mortality, slowing of healing process, and increasing in hospital bills.Objectives: This study aims to determine the predictive factors of HAM.Method: A prospective study was performed. Samples were 1-month-old – 18-years-old children who hospitalized in pediatric ward of Sardjito Hospital in Yogyakarta from February 2023 to April 2023. Samples were taken using a consecutive sampling method. The relationship between variables was presented as odds ratio (OR), confidence intervals of 95%, the score for each variable, and statistical significance levels p < 0.05.Results: 21 of 196 patients were diagnosed as HAM, with a male-to-female ratio of 1.1: 1. The prevalence of HAM was 10.9%. Bivariate analysis showed that maternal education (OR=2.27; CI 95% 1.02 – 5.05; p=0.041), comorbid of congenital heart disease (CHD) (RR=3.31; CI 95% 1.30 – 8.42; p=0,037), and 3rd degree of severity disease (RR=6.00; CI 95% 2.87 – 12.56; p=0.001) was significantly related to HAM. Multivariate analysis showed that comorbid of CHD (OR=5.33; CI 95% 1.34 – 20.7; p=0.017) and 3rd degree of severity disease (OR=11.54; CI 95% 3.52 – 37.86; p=0.000) increased the odds of developing of HAM.Conclusion: Comorbid of CHD and 3rd degree of severity disease increased the odds of developing HAM during hospitalization.